المقاربات السوسيولوجية في المذكرات والرسائل العلمية - حميدي، الطيب (University Of Eloued جامعة الوادي, 2022)
تشغل المقاربة السوسيولوجية اهتمام العلماء والمفكرين في مجالات العلوم الانسانية والاجتماعية عامة وعند علماء الاجتماع بالخصوص, لما لها من وظائف وصفية تفسيرية تنبؤيه لقضايا ومشكلات المجتمع, فالأمر لا يتعلق بالبحث العلمي وحده, بل يتخطاه الى القضايا التي نواجهها جميعا في حياتنا اليومية, في اطار فهمنا لما يجري لنا وللأخرين من حولنا, كما تعمل المقاربة او النظرية على توجيه الدراسة الوجهة العلمية الصحيحة والاهتداء إلى المنهج العلمي الذي يتناسب وطبيعة هذه الدراسة ومجالاتها، وتزودها بالفروض العلمية وتوجهها إلى المراجع العلمية المناسبة وغيرها من العمليات البحثية. ان البحث السوسيولوجي الاصيل يستوجب اتباع خطوات واجراءات معرفية ومنهجية دقيقة التي بدورها تعمل على رسم الاطار البحثي الذي يسير وفقه الباحث, لكن في المقابل وبالنظر الى واقعنا البحثي وما يحكى في هذا المجال تجد الكثير لا يجيدون توظيف النظرية في ابحاثهم, بل اصبحت من المعيقات البحثية لديهم. ومن هذا المنطلق سنحاول من خلال هذه الورقة البحثية (المداخلة) توضيح كيفية توظيف المقاربة السوسيولوجية في المذكرات والرسائل العلمية, وذلك من خلال تقديم مفهوم المقاربة السوسيولوجية وإبراز أهميتها في البحوث الاكاديمية, لنختم الدراسة باقتراح نموذج منهجي مختصر لكيفية توظيفها Abstract: The sociological approach occupies the interest of scholars and thinkers in the fields of human and social sciences in general, and among sociologists in particular, because of its descriptive, explanatory and predictive functions for the issues and problems of society. It runs for us and for others around us, and the approach or theory directs the study in the correct scientific direction and guides to the scientific method that is commensurate with the nature and fields of this study, and provides it with scientific assumptions and directs it to the appropriate scientific references and other research processes. Authentic sociological research requires following precise cognitive and methodological steps and procedures, which in turn serve to draw the research framework according to which the researcher is going, but in return, and given our research reality and what is being said in this field, you find many who are not good at employing theory in their research, but rather it has become one of their research obstacles. . From this point of view, we will try through this research paper (intervention) to clarify how to employ the sociological approach in scientific notes and theses, by presenting the concept of the sociological approach and highlighting its importance in academic research, to conclude the study by suggesting a brief methodological model for how to employ it.
مداخلة
Keywords: البحث العلمي(السوسيولوجي); المقاربة السوسيولوجية; الباحث الاجتماعي; scientific research (sociology); the sociological approach; the social researcher